Sequential requirement of Sox4 and Sox11 during development of the sympathetic nervous system. - Wegner, Michael; Sock, Elisabeth; et al. (Development, 2010)
The highly related transcription factors Sox4 and Sox11 are expressed in the developing sympathetic nervous system. In the mouse, Sox11 appears first, whereas Sox4 is prevalent later. Using mouse mutagenesis and overexpression strategies in chicken, we studied the role of both SoxC proteins in this tissue. Neither Sox4 nor Sox11 predominantly functioned by promoting pan-neuronal or noradrenergic differentiation of sympathetic neurons as might have been expected from studies in neuronal precursors of the central nervous system. The transcriptional network that regulates the differentiation of sympathetic neurons remained intact and expression of noradrenergic markers showed only minor alterations. Instead, Sox11 was required in early sympathetic ganglia for proliferation of tyrosine hydroxylase-expressing cells, whereas Sox4 ensured the survival of these cells at later stages. In the absence of both Sox4 and Sox11, sympathetic ganglia remained hypoplastic throughout embryogenesis because of consecutive proliferation and survival defects. As a consequence, sympathetic ganglia were rudimentary in the adult and sympathetic innervation of target tissues was impaired leading to severe dysautonomia. © 2010. Published by The Company of Biologists Ltd.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.sequen
Keywords: Apoptosis; Chicken; Conditional mutagenesis; Mouse; Noradrenergic differentiation; Proliferation; Sympathoadrenal lineage